Dynamic properties of excitons in ZnO/AlGaN/GaN hybrid nanostructures - Forsberg, Mathias (Sci Rep, 2015)
Hybrid samples based on ZnO colloidal nanocrystals (NCs) deposited on AlGaN/GaN quantum well (QW) structures with different top barrier thickness d = 3, 6 and 9 nm are studied by time-resolved photoluminescence. Thermal behavior of the QW exciton lifetime in the hybrids and in the bare QW structures has been compared and it has been found that the QW exciton recombination rate increases in the hybrid having d = 3 nm and decreases in the hybrid with d = 6 nm, while no change has been observed for the structure with d = 9 nm. It is suggested that non-radiative resonance energy transfer from the QW excitons to the ZnO NCs and a variation of the surface potential can both influence the QW exciton lifetime in the hybrids.